Antimicrobial resistance mechanisms of linezolid resistant staphylococci and enterococci collected in Gauteng, South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2019.